Effectiveness of microwave irradiation on the disinfection of complete dentures - Silva, Mariana Montenegro [UNESP]; Vergani, Carlos Eduardo [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Neppelenbroek, Karin Hermana [UNESP]; Spolidório, Denise Madalena Palomari [UNESP]; Machado, Ana Lucia [UNESP] (My University, 2006)
Purpose: The purpose of this study was to evaluate the effectiveness of microwave irradiation on the disinfection of simulated complete dentures. Materials and Methods: Eighty dentures were fabricated in a standardized procedure and subjected to ethylene oxide sterilization. The dentures were individually inoculated (10 7 cfu/mL) with tryptic soy broth (TSB) media containing one of the tested microorganisms (Candida albicans, Streptoccus aureus, Bacillus subtilis, and Pseudomonas aeruginosa). After 48 hours of incubation at 37°C, 40 dentures were individually immersed in 200 mL of water and submitted to microwave irradiation at 650 W for 6 minutes. Forty nonirradiated dentures were used as positive controls. Replicate aliquots (25 μL) of suspensions were plated at dilutions of 10 -3 to 10 -6 on plates of selective media appropriate for each organism. All plates were incubated at 37°C for 48 hours. TSB beakers with the microwaved dentures were incubated at 37°C for 7 more days. After incubation, the number of colony-forming units was counted and the data were statistically analyzed by Kruskal-Wallis test (α = .05). Results: No evidence of growth was observed at 48 hours for S aureus, B subtilis, and C albicans. Dentures contaminated with P aeruginosa showed small growth on 2 plates. After 7 days incubation at 37°C, no growth was visible in the TSB beakers of S aureus and C albicans. Turbidity was observed in 3 broth beakers, 2 from P aeruginosa and 1 from B subtilis. Conclusion: Microwave irradiation for 6 minutes at 650 W produced sterilization of complete dentures contaminated with S aureus and C albicans and disinfection of those contaminated with P aeruginosa and B subtilis.
Keywords: acrylic acid resin; disinfectant agent; ethylene oxide; Lucitone; poly(methyl methacrylate); Bacillus subtilis; bacterial count; Candida albicans; culture medium; denture; disinfection; instrument sterilization; materials testing; microwave radiation; Pseudomonas aeruginosa; radiation exposure; Staphylococcus aureus; Acrylic Resins; Colony Count, Microbial; Culture Media; Denture Bases; Denture, Complete; Ethylene Oxide; Materials Testing; Microwaves; Polymethyl Methacrylate; Sterilization; Time Factors